2013
DOI: 10.1021/es304729d
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Stability and Electrokinetic Properties of Intrinsic Plutonium Colloids: Implications for Subsurface Transport

Abstract: Subsurface transport of plutonium (Pu) may be facilitated by the formation of intrinsic Pu colloids. While this colloid-facilitated transport is largely governed by the electrokinetic properties and dispersion stability (resistance to aggregation) of the colloids, reported experimental data is scarce. Here, we quantify the dependence of ζ-potential of intrinsic Pu(IV) colloids on pH and their aggregation rate on ionic strength. Results indicate an isoelectric point of pH 8.6 and a critical coagulation concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…For nano-CuO, the shift from positive to negative surface charge that was caused by phosphate may also influence the fate and toxicology of these and other metal oxide ENMs, by altering their interactions with ions and other charged surfaces. For example, clay particles suspended in natural waters can act as carriers for charged particles and transport ENMs much further than they would otherwise, 30 but this effect is very sensitive to changes in electrochemistry 31 and may be altered by changes in ENM surface charge.…”
Section: Methodsmentioning
confidence: 99%
“…For nano-CuO, the shift from positive to negative surface charge that was caused by phosphate may also influence the fate and toxicology of these and other metal oxide ENMs, by altering their interactions with ions and other charged surfaces. For example, clay particles suspended in natural waters can act as carriers for charged particles and transport ENMs much further than they would otherwise, 30 but this effect is very sensitive to changes in electrochemistry 31 and may be altered by changes in ENM surface charge.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is worth pointing out that two recent studies found that the presence of suspended kaolinite particles noticeably increased TiO 2 and plutonium colloids mobilities through sandy porous media (Abdel-Fattah et al 2013;Cai et al 2014). It is believed that due to the intrinsic of engineered NPs and microbe properties, their stabilities in suspensions might be different.…”
Section: Al 2 O 3 and Tio 2 Nps Transport In The Presence Of Kaolinitementioning
confidence: 99%
“…Clay particles have a high potential to interact with other (bio) colloids and could serve as carriers of colloids due to their surface charge heterogeneity (Schroth and Sposito 1997;Vasiliadou and Chrysikopoulos 2011;Syngouna and Chrysikopoulos 2013;Cai et al 2014). Depending on the physicochemical conditions in the porous media, clay particles may facilitate or hinder the mobility of colloids in a study by Yang et al (2012), they found that the presence of bentonite in suspensions significantly reduced the transport of bacteria in the quartz sand porous media while Abdel-Fattah et al (2013) observed that the plutonium colloids transport was facilitated though subsurface soil by presence of smectite clay. Furthermore, Fang et al (2009) evaluated TiO 2 -NP transport through different soil types.…”
Section: Introductionmentioning
confidence: 99%
“…2a), the polymer size decreased over the aging period. Typically, P >450nm declined to ~2% at t = 135 d. This trend towards decreasing sizes was also observed in relatively high concentrations of Pu(IV) polymers (~10 −3 mol/L Pu)(Abdel-Fattah et al, 2013;Ekberg et al, 2013). Such polymers (plutonium oxide nanoclusters) with chemical structures very similar to that of crystalline PuO 2 contained 38…”
mentioning
confidence: 66%
“…Based on the experimental results of DLS and EXAFS, Abdel-Fattah et al (2013) and Ekberg et al (2013) indicated decreased size of aged polymers. However, an opposite trend in their size was shown according to the results of DLS (Triay et al, 1991), XRD (Delegard, 2013), LIBD (Rothe et al, 2004), and ultracentrifuge (Ichikawa and Sato, 1984).…”
Section: Accepted Manuscriptmentioning
confidence: 99%